APPLICATION OF QUARTET CARD MEDIA TO IMPROVE SCIENCE LEARNING OUTCOMES CLASS VIII MTS DARUL ULUM - Umdatul Khoiriyah; Feerlie Mhonthana Indra; Nidia Zuhara (Yayasan Adra Karima Hubbi, 2026)
Science learning at the MTs level still often faces the problem of low student learning outcomes because the learning process tends to take place conventionally, is less interactive, and has not fully encouraged active student involvement. This condition is also found in grade VIII students of MTs Darul Ulum, where most of the students have not reached the completion of learning in science subjects. This study aims to analyze the application of quartet card media in improving the science learning outcomes of grade VIII MTs Darul Ulum students, describe the application process, and identify students' responses to the use of the media. The research uses the Classroom Action Research approach which is carried out in two cycles, with stages of planning, action implementation, observation, and reflection. The research subjects amounted to 22 students in grade VIII. The research instruments included learning outcome tests, observation sheets, structured interviews, and documentation. The results showed that student learning completeness increased from 18 percent in pre-action to 40 percent in cycle I and 86 percent in cycle II. In addition, students show a positive response in the form of increased enthusiasm, cooperation, and activeness during learning. Thus, quartet card media has proven to be effective in improving science learning outcomes while improving the quality of the learning process in a more active, fun, and meaningful way